Development of a Method for Simultaneous Generation of Multiple Genetic Modification in Salmonella enterica Serovar Typhimurium - Jing, Wenxian; Liu, Juan; Wu, Shanshan; Chen, Qiwei; Li, Xuerui; Liu, Yongsheng (Frontiers in Genetics, 2020)
To comprehensively analyze bacterial gene function, it is important to simultaneously generate multiple genetic modifications within the target gene. However, current genetic engineering approaches, which mainly use suicide vector- or λ Red homologous recombination-based systems, are tedious and technically difficult to perform. Here, we developed a flexible and easy method to simultaneously construct multiple modifications at the same locus on the Salmonella enterica serovar Typhimurium chromosome. The method combines an efficient seamless assembly system in vitro, Red homologous recombination in vivo, and counter-selection marker sacB. To test this method, using the seamless assembly system, various modification fragments for target genes cpxR, cpxA, and acrB were rapidly and efficiently constructed in vitro. sacBKan cassettes generated via polymerase chain reaction were inserted into the target loci in the genome of S. Typhimurium strain CVCC541. Resulting pKD46-containing kanamycin-resistant recombinants were selected and used as intermediate strains. Multiple target gene modifications were then carried out simultaneously via allelic exchange using various homologous recombinogenic DNA fragments to replace the sacBKan cassettes in the chromosomes of the intermediate strains. Using this method, we successfully carried out site-directed mutagenesis, seamless deletion, and 3× FLAG-tagging of the target genes. This method can be used in any bacterial species that supports sacB gene activity and λ Red-mediated recombination, allowing in-depth functional analysis of bacterial genes.